2010
DOI: 10.1177/1947601909358722
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution to Neuroendocrine Tumorigenesis of Parallel Egfr Signaling in Cancer Cells and Pericytes

Abstract: Factors associated with tumor sensitivity to epidermal growth factor receptor (EGFR) inhibitors in the context of wild-type EGFR remain elusive. This study investigates the mechanistic basis of responsiveness to EGFR inhibitors in the RIP1-Tag2 (RT2) mouse model of pancreatic neuroendocrine tumorigenesis (PNET). Upon treatment of RT2 mice with EGFR inhibitors, PNET tumors harboring wild-type, nonamplified alleles of Egfr grow at a markedly reduced rate and display a significant increase in tumor cell apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
(94 reference statements)
3
21
0
Order By: Relevance
“…Furthermore, treatment with an inhibitor of EGFR signaling, gefitnib, induced apoptosis in RHAMM B -expressing cells, although we cannot exclude the possibility that this effect may be mediated by inhibition of other uncharacterized kinases. Additionally, it has been shown that EGFR signaling contributes to tumorigenesis in RIP-Tag mice (18). The RHAMM full-length isoform, RHAMM A , enhances serum-induced Erk1/2 phosphorylation in embryonic fibroblasts from RHAMM knockout mice (10), and here we showed that overexpression of RHAMM B phosphorylates Erk1/2 in mouse pancreatic islet tumor cells.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, treatment with an inhibitor of EGFR signaling, gefitnib, induced apoptosis in RHAMM B -expressing cells, although we cannot exclude the possibility that this effect may be mediated by inhibition of other uncharacterized kinases. Additionally, it has been shown that EGFR signaling contributes to tumorigenesis in RIP-Tag mice (18). The RHAMM full-length isoform, RHAMM A , enhances serum-induced Erk1/2 phosphorylation in embryonic fibroblasts from RHAMM knockout mice (10), and here we showed that overexpression of RHAMM B phosphorylates Erk1/2 in mouse pancreatic islet tumor cells.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, increased activity of the EGFR pathway has been identified as a potential resistance mechanism (56,57). It is of note that in addition to dependence on IGF signaling, RIP-Tag2 tumors have also recently been demonstrated to exhibit sensitivity to pharmacological or genetic inactivation of EGFR (58), raising the possibility that signaling via EGFR can also influence the efficacy of IGF pathway targeting strategies in this model. It was surprising that effective blockade of IGF signaling pathways by A12 did not appreciably affect the invasive phenotype of the resultant tumors, in contrast to the proinvasive effects observed upon IGF-1R overexpression (20), perhaps suggesting that IGF-1R can enhance but is not obligatory for cancer cell invasion in this model.…”
Section: Discussionmentioning
confidence: 99%
“…The CAFproduced HB-EGF enhanced cancer cell proliferation. There is a report that HB-EGF plays a role in tumor progression in pericytes in a mouse model of pancreatic neuroendocrine tumorigenesis (35). Therefore, HB-EGF might contribute to cancer progression by various means.…”
Section: Discussionmentioning
confidence: 99%